The age of microfinance: Destroying Latin American economies from the bottom up - Milford Bateman (Austrian Foundation for Development Research (ÖFSE), 2013)
This article argues that the microfinance model that arrived in Latin America in the 1970s has proven, as elsewhere around the world, to be an almost wholly destructive economic and social policy intervention. Centrally, I argue that the microfinance model is responsible for embedding and giving continued impetus to an adverse 'anti-development' trajectory in Latin America's economies, one that has progressively helped to de-industrialise, infantilise and informalise the overall local economic and social structure. Until recently, the extent and precise nature of this 'anti-development' trajectory has been ignored for fear of undermining and delegitimizing the global microfinance model and, with it, the dominant political-economic philosophy - neoliberalism - that essentially gave life to it. Effective local industrial policies and 'pro-development' local financial institutions are now urgently required in Latin America to build genuinely sustainable and equitable solidarity-driven local economies from the bottom up.
Keywords: 330; microcredit; microfinance; neoliberalism; productivity; deindustrialisation; Mikrofinanzierung; Produktivität; Deindustrialisierung; Wirtschaftsliberalismus; Lateinamerika